Чинники впливу на формування доходу підприємства: обліково-аналітичний аспект - Остапенко, Яна Олександрівна; Морозовський, Павло Анатолійович («Придніпровська державна академія будівництва та архітектури», 2020)
Статтю присвячено визначенню та узагальненню чинників впливу на формування доходу підприємства. Доведено важливість їх урахування з позиції обліку та аналізу. Висвітлено врахування чинників впливу під час ведення бухгалтерського обліку. Використовуючи економіко-статистичні методи, аналіз доходів проведено за матеріалами ПАТ «Теремно Хліб». Розрахунки і побудову моделі здійснено за допомогою програмного продукту RStudio. За допомогою економіко-статистичного аналізу проведено аналіз фінансових результатів діяльності ПАТ «Теремно Хліб». За результатами проведеного аналізу з використанням програми RStudio визначено тісноту впливу обсягу реалізованої продукції, собівартості продукції, витрат на збут та матеріальних витрат на підприємстві. Запропоновано шляхи поліпшення фінансових показників діяльності та збільшення доходу підприємства. За результатами трендового аналізу визначено тенденцію та спрогнозовано обсяги отриманого доходу на найближчі періоди. На прикладі ПАТ «Теремно Хліб» продемонстровано практичну корисність визначення, врахування впливу чинників на дохід підприємства з позиції обліку та аналізу.

The article is devoted to identifying and generalizing the factors influencing the formation of the enterprise income and proving the importance of taking them into account and analysis. The efficiency of the enterprise in market conditions is determined by the amount of income received. The level and amount of income are shaped by certain factors. Therefore, the relevance of research into the formation of income and identify the impact of various factors on it is the key in making optimal management decisions to improve the efficiency of the enterprise. The main factors of a manufacturing enterprise include: quantity of produced and sold products, assortment of production, quality of production, cost, level of selling prices, as well as technical and economic factors: cost of raw materials, semi-finished products, fuel and energy, wages. The accounting policies of the enterprise and inflationary processes, as well as taxation, are considered as factors of influence. The purpose of the article is to identify and summarize the factors that affect the income of the enterprise, justify their impact from the point of view of ac- counting and analysis, conduct economic and statistical analysis and forecast income to make optimal management decisions on the example of PJSC «Teremno Khlib». The research used scientific methods based on the dialectical method of knowledge and objective laws of economics. Economic-statistical methods, methods of analysis and modeling were used as well. The model was calculated and built using the RStudio software. According to the results of the analysis, the close influence of the volume of sales, the cost of production, sales costs and material costs at the enterprise is determined. It has been found that the most significant impact on the profit generation of PJSCs is the cost and sales. The ways of improvement of financial indicators of activity and increase of profit of the enterprise are offered. According to the results of the trend analysis, the trend is determined and the amounts of the received income are forecast for the nearest periods of time. On the example of PJSC “Teremno Khlib” the practical usefulness of determining, taking into account the influence of factors on the income of the enterprise from the point of view of accounting and analysis is demonstrated.
Keywords: чинники впливу на дохід; дохід; витрати; аналіз доходу; прогнозування доходу; factors of influence on income; income; expenses; income analysis; income forecasting